2021
DOI: 10.31557/apjcp.2021.22.3.843
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Barbadensis miller and Marsdenia Condurango Extracts Induces Apoptosis Promotes Oxidative Stress by Limiting Proliferation of Cervical Cancer and Liver Cancer Cells

Abstract: Background: Drug synergy is the combine effect of drug efficacy. Synergistic combinations of active ingredients have proven to be highly effective and more useful in therapeutics. In contrast, the individual effect of drug is usually undesirable and mostly used for selecting drug-resistant mutations. Purpose of this study was to check synergistic effects of both plants (Barbadensis miller and Marsdenia condurango) against liver and cervical cancer. Methodology: Culturing of HeLa (cervical cancer cell line) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Furthermore, studies have shown that phytotherapeutic products rich in antioxidants might reduce the risk of cancer. As a result, there is a pressing need to identify novel anticancer drugs derived from plants with significant antioxidant activity [22]. The main goal of this investigation was to discover if Datura metel extracts had any apoptotic, anti-proliferative, and antioxidative activities against the HepG2 cell line in comparison to the normal BHK cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that phytotherapeutic products rich in antioxidants might reduce the risk of cancer. As a result, there is a pressing need to identify novel anticancer drugs derived from plants with significant antioxidant activity [22]. The main goal of this investigation was to discover if Datura metel extracts had any apoptotic, anti-proliferative, and antioxidative activities against the HepG2 cell line in comparison to the normal BHK cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of plant-derived anticancer medicines induce intrinsic or extrinsic apoptosis, as well as caspase and/or p53-dependent or independent processes (19). Annexin V staining reveals a substantial proportion of apoptosis after treatment with plant extracts in multiple studies (6,20). The plants' ethanol and hexane induces increased apoptotic activity in HepG2 cells through annexin V-dependent pathways, resulting in a more apoptotic activity in the cells.…”
Section: In Vitro Assessment Of Antioxidant Activity Of Chrysanthemum...mentioning
confidence: 99%